Reprogramming of glucocorticoid receptor function by hypoxia. (26th October 2021) - Vanderhaeghen, Tineke; Timmermans, Steven; Watts, Deepika; Paakinaho, Ville; Eggermont, Melanie; Vandewalle, Jolien; Wallaeys, Charlotte; Van Wyngene, Lise; Van Looveren, Kelly; Nuyttens, Louise; Dewaele, Sylviane; Vanden Berghe, Joke; et al.
Abstract: Here, we investigate the impact of hypoxia on the hepatic response of glucocorticoid receptor (GR) to dexamethasone (DEX) in mice via RNA‐sequencing. Hypoxia causes three types of reprogramming of GR: (i) much weaker induction of classical GR‐responsive genes by DEX in hypoxia, (ii) a number of genes is induced by DEX specifically in hypoxia, and (iii) hypoxia induces a group of genes via activation of the hypothalamic–pituitary–adrenal (HPA) axis. Transcriptional profiles are reflected by changed GR DNA‐binding as measured by ChIP sequencing. The HPA axis is induced by hypothalamic HIF1α and HIF2α activation and leads to GR‐dependent lipolysis and ketogenesis. Acute inflammation, induced by lipopolysaccharide, is prevented by DEX in normoxia but not during hypoxia, and this is attributed to HPA axis activation by hypoxia. We unfold new physiological pathways that have consequences for patients suffering from GC resistance. Synopsis: This study investigates the impact of hypoxia on hepatic GR function and unfolds new physiological pathways that might have implications for patients suffering from GC resistance. Hypoxia stabilizes HIF1α and HIF2α at the hypothalamus and activates the HPA axis which leads to increased GR‐dependent lipolysis and ketogenesis. Hypoxia induces transcriptional reprogramming of the GR. In hypoxic conditions, DEX is no longer able to protect against acute inflammation. Abstract : This study investigates the impact of hypoxia on hepatic GR function and unfolds new physiological pathways that might have implications for patients suffering from GC resistance.